Pediatric Pneumonia Team-Based Learning Module - Nicole Frei; Kenneth Pituch; Patricia Keefer; Jocelyn Schiller (Association of American Medical Colleges, 2011)
Abstract This resource is a part of a six-module curriculum which uses team-based learning (TBL) approaches to teach medical students clinical applications of general pediatric topics. Included are questions, an answer key, citations for reference articles, and descriptions of how to facilitate and evaluate a team-based learning exercise. This module deals with pediatric pneumonia. The other modules deal with asthma, nutrition, abdominal pain, anemia, and fever. These TBL modules have been used on the third-year pediatric clinical clerkship for 1 year as part of the core pediatric curriculum at the University of Michigan Medical School. Faculty and student suggestions for improvements in both the reading material and exercises have been incorporated over the course of the year to enhance the modules. Our analysis indicates that student performance on the NBME examinations and on the clerkship overall has remained consistent after inclusion of TBL into the clerkship curriculum. The pilot trial of this exercise is in the process of being formally evaluated as part of a prospective study comparing TBL with lectures.